In situ rheology of yeast biofilms - Brugnoni, Lorena Inés (2014)
The aim of the present work was to investigate the in situ rheological behavior of yeast biofilms growing on stainless steel under static and turbulent flow. The species used (Rhodototula mucilaginosa, Candida krusei, Candida kefyr and Candida tropicalis) were isolated from a clarified apple juice industry. The flow conditions impacted biofilm composition over time, with a predominance of C. krusei under static and turbulent flow. Likewise, structural variations occurred, with a tighter appearance under dynamic flow. Under turbulent flow there was an increase of 112 μm in biofilm thickness at 11 weeks (p < 0.001) and cell morphology was governed by hyphal structures and rounded cells. Using the in situ growth method introduced here, yeast biofilms were determined to be viscoelastic materials with a predominantly solid-like behavior, and neither this nor the G’0 values were significantly affected by the flow conditions or the growth time, and at large deformations their weak structure collapsed beyond a critical strain of about 1.5–5%. The present work could represent a starting point for developing in situ measurements of yeast rheology and contribute to a thin body of knowledge about fungal biofilm formation.